Evaluation of interprofessional relational coordination and patients' perception of care in outpatient oncology teams. Issue 2 (4th March 2017) - Azar, Jose M.; Johnson, Cynthia S.; Frame, Amie M.; Perkins, Susan M.; Cottingham, Ann H.; Litzelman, Debra K.
ABSTRACT: This pilot study was designed to measure teamwork and the relationship of teamwork to patient perceptions of care among 63 members of 12 oncology teams at a Cancer Centre in the Midwest. Lack of teamwork in cancer care can result in serious clinical errors, fragmentation of care, and poor quality of care. Many oncology team members, highly skilled in clinical care, are not trained to work effectively as members of a care team. The research team administered the Relational Coordination survey to core oncology team members—medical oncologists, nurse coordinators, and clinical secretaries—to measure seven dimensions of team skills (four relating to communication [frequency, timeliness, accuracy, and problem solving] and three relating to relationship [shared goals, shared knowledge, and mutual respect]) averaged to create a Relational Coordination Index. The results indicated that among the team member roles, nurse coordinator relational coordination indices were the strongest and most positively correlated with patient perception of care. Statistically significant correlations were intra-nurse coordinator relational coordination indices and two patient perception of care factors (information and education and patient's preferences). All other nurse coordinator intra-role as well as inter-role correlations were also positively correlated, although not statistically significant.